HUBUNGAN SELF-CONTROL DENGAN INTENSITAS BERMAIN GAME ONLINE PADA SISWA SMP PGRI NGORO MOJOKERTO - Fitri Auliya Nurul Izza; Hazim Hazim (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the relationship  of Self-control with the intensity of playing online games in SMP PGRI Ngoro students. The intensity of playing  online games  is the duration and frequency used to play online games. In reality, online game users are not a few students who are  excessive in playing online games, this should be balanced with Self-control in  each student to be able to restrain, regulate impulses, and behavior in order to avoid negative consequences due to excessive intensity of playing online games. This study used quantitative methods, with participants as many as 105 students who played online games at SMP PGRI Ngoro with an age range of 11-14 years. The hypothesis test shows that there is a significant and negative relationship between the Self-control variable  and the intensity variable of playing online games. This means that the higher  the Self-control, the lower the intensity of playing online games. Vice versa, the lower the Self-control,  the higher the intensity of playing online games.